2022
DOI: 10.1097/icb.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cystoid Macular Edema Following Bimatoprost Implants

Abstract: To report the development of bilateral cystoid macular edema after bimatoprost implant (Durysta) injections in both eyes to treat primary open-angle glaucoma.Methods: Case report.Results: A 93-year-old woman with a history of primary open-angle glaucoma received bimatoprost implant (Durysta) injections in both eyes 4 weeks apart. The patient subsequently developed progressively decreased visual acuity in both eyes because of bilateral cystoid macular edema, which improved with topical corticosteroid therapy.Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Although 1 patient experienced both ME and ocular inflammation during OMDI treatment, both AEs were classified as moderate and were resolved during the study. Similar to the case following OMDI treatment in this study, one case of bilateral ME was reported recently in a patient with POAG following bimatoprost implant injections 17 . In another study of OMDI, all cases of treatment-related ME occurred in eyes with intraocular lens implants 18 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although 1 patient experienced both ME and ocular inflammation during OMDI treatment, both AEs were classified as moderate and were resolved during the study. Similar to the case following OMDI treatment in this study, one case of bilateral ME was reported recently in a patient with POAG following bimatoprost implant injections 17 . In another study of OMDI, all cases of treatment-related ME occurred in eyes with intraocular lens implants 18 .…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the case following OMDI treatment in this study, one case of bilateral ME was reported recently in a patient with POAG following bimatoprost implant injections. 17 In another study of OMDI, all cases of treatment-related ME occurred in eyes with intraocular lens implants. 18 PAPs, such as eyelid pigmentation, eyelash growth, and deepening of the upper eyelid sulcus have been reported with FP agonists, and OMDI is associated with a lower frequency (0%-2%) of these PAPs compared with FP agonists.…”
Section: Discussionmentioning
confidence: 95%
“…Patel et al reported also a case report of bilateral CME following bimatoprost implant. 8 The patient was treated with topical corticosteroid with improvement and resolution of the edema.…”
Section: Discussionmentioning
confidence: 99%